Experience and advice consequences shape information sharing strategies - Hernán Anlló; Gil Salamander; Nichola Raihani; Stefano Palminteri; Uri Hertz (Communications Psychology)
Abstract Individuals often rely on the advice of more experienced peers to minimise uncertainty and increase success likelihood. In most domains where knowledge is acquired through experience, advisers are themselves continuously learning. Here we examine the way advising behaviour changes throughout the learning process, and the way individual traits and costs and benefits of giving advice shape this behaviour. We ran a series of experiments implementing a decision task within a reinforcement learning framework, where participants could decide to share their choices as advice to others. Participants were overall likely to share their choices as advice, even on the first trial before learning. Tendency to share advice and advice quality increased as advisers learned about the value of choices, and moved from exploratory to exploitative behaviour. The introduction of consequences to advising resulted in a shift of the overall tendency to give advice, lowering it when advising implicated monetary loss, and increasing it when advising held reputational value. Individual differences in social anxiety levels were associated with lower tendency to share exploratory decisions. Our results show that advisers tend to share choices that are backed by their own experience, but that this relationship can be altered by advice-consequences and individual traits.